PENGARUH BPJS KETENAGAKERJAAN DALAM MENINGKATKAN KESEJAHTERAAN TENAGA KERJA - Hafiz Sutrisno (Universitas Pahlawan, 2020)
Workers in Indonesia now really need a social security for themselves, because with the social security received by them makes them more focused in carrying out their duties to completion. The existence of social security provided will increase the welfare of the workforce itself and have a good impact on the survival of their families in the future if one day there is an accident of work from these workers when they carry out their duties the family can enjoy financial assistance from the government through social security. This study uses qualitative methods, namely research procedures that produce descriptive data in the form of written or spoken words from people or observable behavior. This method also comes from actions that are used as an understanding based on phenomena that occur in society, especially workers. In giving effect to the workers, BPJS Ketenagakerjaan has functions for workers, namely: Organizing work accident insurance programs, Organizing death insurance programs, Conducting old age insurance programs, Organizing pension insurance programs. The conclusion of this research is that there are still many companies that do not give rights to their workforce, that is, they do not take care of BJPS Ketenagakerjaan, which is a matter that must be obtained by each workforce. And the lack of awareness of the workforce about the benefits of BPJS Ketenagakerjaan for them in the event of a work accident.